2019
DOI: 10.1038/s41419-019-1326-6
|View full text |Cite
|
Sign up to set email alerts
|

MiR-30a regulates cancer cell response to chemotherapy through SNAI1/IRS1/AKT pathway

Abstract: Despite gemcitabine being the leading chemotherapeutic drug for pancreatic cancer, many patients still relapse due to the drug resistance. We previously reported the molecular link between FKBP51 mediated AKT inhibition and gemcitabine response in pancreatic cancers. However, the upstream regulator of this pathway, especially the involvement of non-coding RNAs in gemcitabine response is still not clear. Here we delineated the miRNA expression profile and key signaling pathways associated with gemcitabine respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 60 publications
2
34
0
Order By: Relevance
“…Importantly, inhibition of miR-26a-5p in vivo caused synucleinopathy and loss of dopaminergic neurons, whereas its overexpression alleviated behavioural abnormalities in a mouse prototype of Parkinson’s disease (PD) [ 67 ].The miRNA-30a acts as a tumour suppressor in glioma [ 68 ], and vital for ubiquitin-proteasome mediated proteolysis (UPP), which has significance in AD and dementia [ 69 ]. In addition, overexpression of miR-30a results in the upregulation of the FOXO signalling pathway [ 70 ], which can mediate beneficial effects through the upregulation of the longevity protein silent mating type information regulation 2 homolog 1 (SIRT1) [ 71 ]. The miRNA-181-5p plays a role in hippocampus-dependent memory formation via inhibition of protein kinase AMP-activated catalytic subunit alpha 1 (PRKAA1), and overexpression of miR-181 enhances memory formation [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, inhibition of miR-26a-5p in vivo caused synucleinopathy and loss of dopaminergic neurons, whereas its overexpression alleviated behavioural abnormalities in a mouse prototype of Parkinson’s disease (PD) [ 67 ].The miRNA-30a acts as a tumour suppressor in glioma [ 68 ], and vital for ubiquitin-proteasome mediated proteolysis (UPP), which has significance in AD and dementia [ 69 ]. In addition, overexpression of miR-30a results in the upregulation of the FOXO signalling pathway [ 70 ], which can mediate beneficial effects through the upregulation of the longevity protein silent mating type information regulation 2 homolog 1 (SIRT1) [ 71 ]. The miRNA-181-5p plays a role in hippocampus-dependent memory formation via inhibition of protein kinase AMP-activated catalytic subunit alpha 1 (PRKAA1), and overexpression of miR-181 enhances memory formation [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the potential of these two circRNAs in tumours remains to be determined. 32,33 Therefore, miRNA-203 may modulate drug resistance by repressing IRS1 at the posttranscriptional level. miRNA-203 is also underexpressed in chemotherapyresistant tumour cells, and lentiviral overexpression of miRNA-203 reverses drug resistance in pancreatic and breast cancers, 31 indicating that loss of miRNA-203 is related to the development of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a plethora of evidences suggest that miRNAs play a significant role in the development of tumors 1113. The dysfunction of miRNAs interferes with gene expression at the post-transcriptional level, resulting in deregulation of tumor growth, metastasis, and drug resistance 14,15. For example, Guo et al have demonstrated that miRNA-532-3p can inhibit the gastric cancer cell proliferation via suppressing the expression of Rab3IP 16.…”
Section: Discussionmentioning
confidence: 99%